God for the 21st century - Stannard, Russell (Philadelphia : Templeton Foundation Press, 2000)
Through a collection by essays of scientists and religious leaders, this book presents a challenging understanding of God and of God's interaction with the world and with ourselves.
A creation story for our times / Ted Burge -- The alpha and the omega of space and time / Rod Davies -- What happened before the big bang? / Paul Davies -- Big and old and dark and cold / Michael Poole -- Ingredients for life / Owen Gingerich -- An icon for the millennium / Bruno Guiderdoni -- Why does the universe work? / Howard Van Till -- A revealed but hidden God / Carl Feit -- Meaning makes a comeback / Gregg Easterbrook -- Did Darwin kill God? / Sam Berry -- The disguised friend
Keywords: Religion and science; God for the 21st century